Birds of a Feather: A Case Study of Friendship Networks of Mainland Chinese College Students in Hong Kong. (August 2015) - Ruan, Danching; Zhu, Shu
We examine the formation process of friendship networks of Mainland Chinese undergraduates in Hong Kong. The data comes from a 2011 survey of Mainland undergraduates at a university in Hong Kong and from in-depth interviews with students. We found a strong in-group pattern in the friendship networks of these students. More than 60% do not have good local friends. On a campus where nearly 90% of the students are locals, on average, only 18% of the good friends named by Mainland students are locals. We find that cultural differences—such as the language barrier, differences in values and ideologies, and differences in academic orientation and future plan—discourage formation of intergroup friendship. But intergroup contacts, as indicated by participation in local organizations, have positive effects on intergroup friendship formation. Both contact opportunities and their timing (i.e., when they become available) are important. During their first year, Mainland students have many more opportunities to interact with other Mainlanders than with local students. This may also be an important factor accounting for the strong in-group pattern in Mainland students' friendship networks.